The Influence of Family Welfare on Work Motivation and Its Impact on the Performance of Private High School Teachers in Jambi - Kuswanto Kuswanto; Refnida Refnida (Universitas Negeri Malang, 2024)
Teacher performance greatly determines school performance in providing educational services to stakeholders. Improving teacher performance must be seen as a shared interest between educational institutions and the government. This research examines the influence of family welfare on work motivation and its impact on teacher performance. The research was conducted using a survey method among teachers at private high schools in Jambi of Indonesia. Respondents were selected randomly after sampling the entire population using area sampling techniques, namely 120 out of 239 teachers. Data were analyzed using the PLS-SEM model. The results of the analysis show that the family welfare of private high school teachers in Jambi has an indirect influence through work motivation on teacher performance. Work motivation has a prominent role in improving teacher performance. The higher the level of family welfare, the greater the teacher's work motivation and the higher the teacher's work motivation, the greater the performance. The results of this research also provide practical implications for educational management institutions or foundations in improving teacher performance through increasing family welfare and work motivation. Keywords: Family welfare, Work motivation, Teacher performance